Beyond Problem Solving: Reconceptualizing the Work of Public Deliberation as Deliberative Inquiry. Issue 1 (14th April 2015) - Carcasson, Martín; Sprain, Leah
Abstract: This article introduces deliberative inquiry (DI), a practical theory designed to guide the work of deliberative practitioners working in their local communities to better address wicked problems by improving the quality of public discourse. DI reconceptualizes the work of public deliberation as sparking and sustaining a unique form of inquiry suited to addressing wicked problems. DI moves from a linear event-focused model where deliberation produces refined public opinion and decision outcomes to using deliberative principles to guide a cyclical learning process. DI seeks to improve community decision making by focusing on obstacles to deliberative engagement, deliberative tensions inherent to wicked problems, and resources for collaborative action. Understanding of these elements is refined throughout the 4 tasks of the deliberative cycle.